Influence of the seeding rate of common oats on the weed infestation - Osipova Valentina; Platonova Agafya; Olesova Marianna; Khiterkheeva Nadezhda; Dondokov Yuri; Matveev Ivan; Pakhomov Viktor; Filippov Vladimir (BIO Web of Conferences)
The article examines the influence of the seeding rate of oats on the weed infestation of oat crops when growing it for green fodder. The aim of the research was to determine the seeding rate of oats when growing for green mass to reduce weed infestation of its crops in Central Yakutia. As a result of research for 2022-2024, the optimal seeding rate of oats in growing for green mass in Central Yakutia was set. It was noted that a reduced seeding rate (4.0mln pcs per 1ha) of oats significantly increases the number of weeds. And a seeding rate of 6.0 mln pcs/ha reduces the weed infestation of oats in growing it for green mass, ensuring a maximum productivity of green mass up to 118 hkg/ha or 11.8 t/ha.